A organização textual da opinião em textos dissertativos acadêmicos, notícias jornalísticas e crônicas do cotidiano - Silva, Rodrigo Leite da (2010)
Aim: This study, situated in the studies of the Portuguese language, aims to contribute to studies dealing with the textual construction of belief in (1) essay in academic and scientific texts and popular science, (2) text news journalistic and (3) chronicles of everyday life. Methodology: The research follows a theoretical-analytical, in which we adopted the theoretical postulations of Text Linguistics, complemented by Critical Discourse Analysis, with socio-cognitive aspects. Justification/ Hypothesis: Although the essay is the focus of constant interest to scholars of the text, treat it as a class opinionated, grouping types of texts opinionated modified by genres, though, is a spongy ground. There is, by definition that the textual construction of belief, it changes depending on the gender discourse in the category of explanation, the schema of textual argument. Results: The analysis indicates that the essay is a text in class opinionated, which changes depending on the conditions of discursive production, in a textual outline of a thesis and two theses. In both modifications, the legitimacy of the arguments is attributed to Marco of Social Cognitions and it is from, which are built to strengthen the arguments. The arguments used travel necessity, possibility and probability. The text presents a journalistic news organization opinionated, based on the interests of the newspaper company, from small text (headline, hairline, eye and lead). And the chronicles of everyday life, are guided by the focusing of the chronicler, in assessing the Mark of the Social Cognitions